Prescription of antipsychotics and prevalence of metabolic syndrome in Vietnamese inpatients with schizophrenia - Nguyen Thi Minh Thuan; Tran Duy Khoa; Chau Van Tuan (Faculty of Pharmacy, Mahidol University, 2022)
Schizophrenia is a severe mental illness, characterized by psychotic symptoms including delusions, hallucinations, dystonia, adolescent behavior and language, and is accompanied by severe functional impairments. Antipsychotics, which are used mainly in the treatment of schizophrenia, have contributed to the development of metabolic syndrome. Studies on metabolic syndrome in schizophrenic patients have been still limited in Vietnam. The objective of this study was to investigate the prevalence of metabolic syndrome in Vietnamese inpatients with schizophrenia. The study population of this descriptive cross-sectional study was all patients with schizophrenia from September 2020 to June 2021 at Inpatient Department of Binh Dinh Provincial Psychiatric Hospital in Viet Nam. Three hundred and twelve patients who met the sampling requirements were enrolled in this study. The prevalence of schizophrenia in female patients was lower than in male patients (36.9% vs. 63.1%) in our study. The prevalence of metabolic syndrome was 30.4% (25.9% in men and 38.3% in women), more in patients ≥40 years old than in patients under 40 years old (the highest prevalence in patients ≥60 years). There was a significant relationship between age, body mass index (BMI), and duration of antipsychotic treatment with the frequency of metabolic syndrome. In conclusions, the prevalence of schizophrenia was higher in male inpatients than in female inpatients. However, the prevalence of metabolic syndrome was higher in female inpatients than male inpatients with schizophrenia, and increased with age, BMI, and duration of antipsychotic treatment.